Socialist Republic of Vietnam Study on e‐ID Infrastructure to Improve Public Services Delivery : Electronic Identification Technical Report - World Bank (Washington, DC, 2015)
This study presents the vision and implementation recommendations for the electronic identity based service delivery framework (EISDF) in Vietnam. It also delineates the roles to be played by the diverse stakeholders (private, public, development community, etc.) in the field. The study recommends various relevant and innovative electronic identity (eID) services that can be implemented to transform and enhance the accountability and efficiency of service delivery across sectors. These recommendations are based on the stocktaking of international experiences and identified possibilities based on the country assessment. Special emphasis is placed on eID systems that operate on mobile phones, and on those that have the potential of being scaled up by both the public and private sectors in Vietnam. The eID systems can help reduce identity fraud and enable individuals to avail of services more securely in a variety of contexts as in mobile banking and mobile applications for health care.